Parâmetros hematológicos e concentração de óxido nítrico salivar em atletas de Jiu Jitsu: um estudo observacional - Agricola, Nestor Persio Alvim (2016)
Physical exercise is considered an important variable in the study of human health, especially due the changes induced in several biomarkers. In physical training, body adaptations are quite specific for each type of sport and effort. The quantification of biochemical parameters related to human health, mediated by physical activity in its many variations, provides new scientific eyes, not only for what relates to the interaction between the various systems, but also in relation to physiological and adaptive effects generated by them. This research consists of the systematic monitoring of Jiu Jitsu athletes, quantifying the variations of some biochemical parameters linked to health, in an attempt to assess the modality of sport in its potential for health and verify the variations in these parameters depending on the type and intensity of the effort and the special characteristics of the sport. Jiu Jitsu is a kind of sport that has gained prominence and become popular. Throughout the year of training, athletes alternate periods of high intensity training with low intensity periods. The energy expenditure is high and the maximum or submaximal effort often leads to muscle, joint and bone injuries. This is a longitudinal descriptive observational study of measurement that had the participation of 14 volunteers who were monitored for 9 months in their training routine. Blood and saliva samples were collected and the heart rate was monitored throughout this period. Saliva was used to quantify nitric oxide and blood for hematological parameters. The results of the experiments were submitted to statistical tests. Hematological parameters of the red series are influenced by the physical effort when performed in a long-lasting mode, during the training period, responding to the intensity of the effort made. The white series, related to the immune system, is influenced acutely, responding to the exercise stimulus with significant changes as the effort is more or less intense. The production of NO in the organism tends to follow the level of effort made; however, the modality studied has the characteristic of promoting the stimulation of the sympathetic nervous system, what reduced the activity of salivary gland and nitrite concentrations after training is performed. Musculoskeletal injuries are typical of this kind of sport and very typical, which ends up modulating partly the organic response to training. This stimulation, however, must be seen as positive for activating the adaptive response and the interaction of several systems.